Human resource management practices of nurse managers and its relationship to the job satisfaction of staff nurses in Private Hospitals - Arevalo, Zheyrille A; Singson-Denosta, Marian Filomena B; Babaran, Jestine Kate G; Eslabon, Kayla Marie M; Alconcer, Inosencia A; Santos, Jonalyn P (South East Asia Nursing Research, 2024)
Effective HRM practices are a critical factor that influences job satisfaction, especially in the nursing field. However, there is a dearth of literature on these studies conducted in the northern part of the Philippines and a need to highlight the implementation challenges or weaknesses of HRM practices across healthcare settings, such as private hospitals. This study assessed the implementation of Human Resource Management (HRM) practices by nurse managers and its relationship to the job satisfaction of staff nurses working in private hospitals in a component city in the northern part of the Philippines. The researchers adopted a descriptive correlational research design. A total of 137 staff nurses from the six private hospitals in Tuguegarao City were included and selected through a convenience sampling technique. Data collection was done using a structured questionnaire which assessed the HRM practices of nurse managers along five dimensions (training and development, performance assessment, career planning, employee participation, and job definition) and the overall job satisfaction of the staff nurses. Results were analyzed using frequency and percentage, mean, T-test, one-way ANOVA, and Pearson r. Results showed that good implementation of HRM practices by nurse managers in private hospitals was included in the study. Moreover, staff nurses are satisfied with their jobs. Additionally, the difference in job satisfaction of the staff nurses was only influenced by their highest educational attainment and all dimensions of HRM practices assessed have a significant positive correlation with the job satisfaction of the staff nurses. It can be concluded that the job satisfaction of staff nurses employed in private hospitals is greatly affected by how nurse managers implement human resource management activities. However, improvements in identifying training needs, provision of timely performance appraisals, clear career directions and job descriptions, and participation in work-related decision-making for staff nurses may be considered by nurse managers.